Cre recombinase affects calcium dynamics already in young mice - Liffers, János Levin; Reinhardt, Jan Peter; Seidl, Matthias Dodo; Kirchhefer, Uwe; Müller, Frank Ulrich; Schulte, Jan Sebastian (Frontiers in Pharmacology, 2025)
BackgroundThe Cre/LoxP system is widely used in cardiovascular research to generate mouse models with tissue-specific inactivation of target genes. Studies have reported that expression of Cre recombinase under the αMHC promoter leads to age-dependent cardiotoxicity with ventricular hypertrophy, fibrosis and ventricular dysfunction at 6 months of age. This study explores the impact of Cre expression on intracellular Ca2+ dynamics in ventricular myocytes of αMHC-Cre mice as early as 3 months old.MethodsMice expressing Cre under the αMHC promoter (CRE) were compared to wild-type (WT) controls. Ventricular cardiomyocytes (VCMs) were isolated by the Langendorff method. Ca2+ transients and sarcomere shortening were simultaneously recorded from VCMs. Ventricular and atrial weights were assessed, VCM dimensions analyzed, and protein and mRNA levels of key proteins involved in Ca2+ dynamics measured by immunoblot analysis and quantitative real-time RT-PCR.ResultsAt 3 months, CRE mice showed no evidence of cardiac hypertrophy. Ventricular or atrial weights and VCM size were not different between CRE and WT mice. The same applied to protein levels of SERCA2a, NCX1, Cav1.2, PLN and its phosphorylated form PLN pThr17. Nevertheless Ca2+ dynamics were significantly altered in CRE mice. Under basal conditions resting and peak Ca2+ were reduced and Ca2+ transient decay was delayed up to 30% in VCMs from CRE vs. WT mice. These differences persisted upon stimulation with 1 µM isoproterenol, whereas Ca2+ transient amplitude increased in CRE VCMs. We confirmed a previously reported reduction in dystrophin, potentially explaining the changes in Ca2+ dynamics. Despite these changes sarcomere shortening parameters were not different between groups.ConclusionAs early as 3 months of age, Cre expression in VCMs leads to changes in Ca2+ dynamics that do not yet affect sarcomere shortening and cannot be attributed to the regulation of key proteins involved in Ca2+ dynamics. Because changes in intracellular Ca2+ dynamics can affect gene expression through altered excitation-transcription coupling, researchers should be aware of these subtle changes that precede the prominent phenotype at 6 months of age. Therefore, it is essential to use Cre-positive mice as controls when analyzing knockout models generated by the Cre/LoxP system.